Optimalisasi Pelayanan Publik Sertifikat Laik Fungsi melalui SIMBG dan Dukungan Tim Profesi Ahli di Kabupaten Pekalongan - Esti Yuwana Pambudi; antonius antonius; prabowo setiyawan (UNISSULA Semarang, 2025)
The Certificate of Feasibility of Function (SLF) is a crucial instrument to ensure building safety, comfort, and compliance; however, achieving public service targets in Pekalongan Regency still faces governance challenges. Digitalization through the Building Management Information System (SIMBG) and support from the Expert Professional Team (TPA) is considered strategic for enhancing service effectiveness. This study aims to analyze the effect of SIMBG implementation on the effectiveness of SLF public services, with TPA support as a moderating variable. An explanatory quantitative approach was employed, surveying 120 respondents, including SLF applicants, service providers, and TPA members. Data were analyzed using structural equation modeling (SEM-PLS) to examine the relationships among variables. The results indicate that SIMBG implementation has a significant positive effect on user satisfaction (β = 0.46; p < 0.01), while TPA support strengthens this relationship (β = 0.31; p < 0.05). The integration of SIMBG and TPA proved effective in enhancing accountability, accelerating service processes, and reducing policy-practice gaps. However, procedural consistency and human resource limitations at the operational level remain. In conclusion, improving SLF service targets requires an integrated approach with SIMBG as a technological enabler and TPA as a professional enabler. Recommendations include enhancing digital literacy among officials, refining technical regulations, and strengthening the role of TPA in procedural assistance. This study is limited to the context of Pekalongan Regency; thus, generalization should be cautious, and future research is recommended to expand locations and include additional variables such as leadership and central regulations to enrich the understanding of SLF governance in Indonesia.